(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess the impact of social media on eating behaviors and identify associated factors among students at Hanoi Medical University in 2024–2025. Methods: A cross-sectional descriptive study was conducted on 490 full-time medical students. Data were collected using convenience sampling via an online survey. The 22-item Scale of Effects of Social Media on Eating Behaviour (SESMEB) was utilized to quantify the impact of social media. Statistical analysis and multivariable linear regression were performed. Results: The mean SESMEB score of the students was 53.42 ± 13.07. Social media exerted the strongest impact on visual stimulation and food information seeking. The multivariable regression model identified five factors significantly associated with an increased SESMEB score: moderate/severe insomnia, alcohol/coffee consumption, social media usage for more than 6 hours/day, independent living, and examination pressure. Conclusions: Social media has a moderate impact on the eating behaviors of students. School health intervention programs require a comprehensive approach to address the combined cluster of high-risk lifestyle behaviors: insomnia, academic pressure, living away from home, and stimulant use.